1989
DOI: 10.1557/proc-165-145
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Epitaxial Silicon Deposition at 220-400°C Using Remote Plasma-Enhanced Chemical Vapor Deposition

Abstract: In this paper the reaction kinetics of Remote Plasma-enhanced Chemical Vapor Deposition (RPCVD) are investigated. Growth rate characterization has been performed for substrate temperatures of 220 – 400°C, r-f powers from 4 – 8 W, and silane flow rates of 10 – 30 sccm. Growth rate has been found to increase exponentially with r-f power, which is, as yet, unexplained. An approximate square root dependence of growth rate on silane partial pressure agrees with the theory of Claasen et. Al for Chemical Vapor Deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The process sequence is typically an RCA (or HF-based) wet chemical clean followed by an in situ H-plasma clean. [2][3][4][5][6][7][8][9] In another related study it was demonstrated that an electron cyclotron resonance (ECR) H-plasma exposure can be effective without a requiring a wet chemical preparation. 1~ Comparing the Auger electron spectroscopy (AES) data before and after H-plasma exposure, the resulting surface exhibits reduced concentrations of carbon and oxygen.…”
Section: -~mentioning
confidence: 99%
“…The process sequence is typically an RCA (or HF-based) wet chemical clean followed by an in situ H-plasma clean. [2][3][4][5][6][7][8][9] In another related study it was demonstrated that an electron cyclotron resonance (ECR) H-plasma exposure can be effective without a requiring a wet chemical preparation. 1~ Comparing the Auger electron spectroscopy (AES) data before and after H-plasma exposure, the resulting surface exhibits reduced concentrations of carbon and oxygen.…”
Section: -~mentioning
confidence: 99%
“…However, the wet processes can leave organic residues and a thin layer of native oxide on the surface due to exposure to ambient conditions, while the vacuum/dry processing steps can take over 30 minutes to perform. One technique, which overcomes this issue, involves the use of an in-situ plasma source to remove carbon and oxygen present on the surface (6).…”
Section: Introductionmentioning
confidence: 99%